Pendekatan Makna Dalam Tafsir Mafātīḥ Al-Ghayb: Kajian Terhadap Rasionalitas Penafsiran Al-Rāzī - Sulfadli; Andi Abdul Hamzah; Abdul Rahman Sakka (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
This article examines the rationality of Fakhr al-Dīn al-Rāzī's exegesis in Mafātīḥ al-Ghayb as a model of meaning-making that integrates revelatory authority with burhānī reasoning. The central problem addressed is how al-Rāzī constructed an exegetical method saturated with kalam argumentation, Aristotelian logic, and natural knowledge without detaching from the textual and transmitted tradition. Employing a qualitative library-based method with a historical-hermeneutical approach, this study examines the primary text of Mafātīḥ al-Ghayb alongside more than thirty recent secondary sources to map this pattern of rationality. The findings indicate that al-Rāzī's rationality is moderately Ash'arite, positioning reason as an instrument for defending and elucidating revelation rather than as an independent authority as held by the Mu'tazilites. This pattern appears in his use of imaginary dialogue, the mas'alah-bahth classification, ta'wīl of ambiguous verses, and the integration of munāsabah, philosophy, and natural science into exegesis. The article argues that al-Rāzī's rationality offers a paradigm relevant to contemporary discourse on the relationship between reason and revelation, while serving as a critical reference for developing an integrative epistemology of tafsir amid the challenges of modern scientific secularization.